A View Inside Corporate Risk Management - Bodnar, Gordon M.; Giambona, Erasmo; Graham, John R.; Harvey, Campbell R. (Management Science, 2019)
Why do firms manage risk? According to various theories, firms hedge to mitigate credit rationing, to alleviate information asymmetry, and to reduce the risk of financial distress. However, empirical support for these theories is mixed. Our paper addresses the “why” by directly asking the managers that make risk management decisions. Our results suggest that personal risk aversion in combination with other executive traits plays a key role in hedging. Our analysis also indicates that risk-averse executives are more likely to rely on (more conservative) fat-tailed distributions to estimate risk exposure. While most theories of risk management ignore the human dimension, our results suggest that managerial traits play an important role. This paper was accepted by Karl Diether, finance.